Support for the US Endangered Species Act Is High and Steady Over the Past Three Decades - John A. Vucetich; Jeremy T. Bruskotter; Robyn Wilson; L. Mark Elbroch; Adam Feltz; Thomas Offer‐Westort (Conservation Letters, 2025)
ABSTRACT Conservation professionals expect increased attempts to weaken the US Endangered Species Act (ESA) during the second Trump administration. As such, it is important to understand Americans’ level of support for the ESA. Prior research indicates that support for the ESA remained consistently strong across four studies conducted over a two‐decade period, 1996–2015. The research presented here extends those observations to six studies conducted over a three‐decade period, 1996–2025. We find that support of the ESA over that period has remained consistently high, at about 84%, and opposition has remained consistently low, at about 12%. We also report on other trends and patterns in support for the ESA, highlighting high and growing support for the ESA among politically conservative people and the absence of any rural–urban divide in support for the ESA.